PKM PEMBIMBINGAN UMKM PADA USAHA MINYAK MAMA, DESA RUMAH SUMBUL, KEC. SINEMBAH TJ. MUDA HULU, KABUPATEN DELI SERDANG, SUMATERA UTARA - Rizki Syahputra; Andam Lukcyhasnita; Meryatul Husna (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Minyak Mama is a Karo Oil UMKM which was founded in 1998. The UMKM is located in the village of Rumah Sumbul, Sinembah District, Tanjung Muda Hulu, Deli Serdang Regency. The processing, management, and marketing methods for these SMEs are classified as traditional. Even so, in terms of management, they have used computers and the internet, but they have not been well organized, especially in accounting and marketing due to the limited knowledge and knowledge of the owners and their working members regarding the use of information technology. Even so, the owners of Minyak Mama have a desire to continue to advance and develop because they are aware of the opportunities and potential in the market, one of the proofs is that they have made packaging neater and more economical, so that they can be marketed to a wider market, to reach more buyers. However, that is not enough. Therefore, to be able to continue to compete, researchers want to offer technical guidance to these SMEs. Especially in management guidance and digital marketing. The stages of activities carried out in this PKM consist of, surveys/observations to find out and explore further the problems of Minyak Mama SMEs, then provide guidance in re-branding the Minyak Mama logo and redesigning the packaging so that the MSME image is more prominent, then marketing training is carried out. digitally and financial bookkeeping training in accordance with applicable Financial Accounting Standards. From this activity, several mandatory outputs are planned including: Increased partner empowerment, in the status achieved; Publication of National Journal with Submitted status; Print Mass Media publications in the form of articles in local newspapers, namely Waspada; Publication of Video Implementation of Activities online such as on Youtube.